FLIm-Guided Raman Imaging to Study Cross-Linking and Calcification of Bovine Pericardium - Shaik, Tanveer Ahmed; Alfonso-Garcia, Alba; Zhou, Xiangnan; Arnold, Katherine M.; Haudenschild, Anne K.; Krafft, Christoph; Griffiths, Leigh G.; Popp, Juergen; Marcu, Laura (Analytical Chemistry, 2020)
Bovine pericardium (BP) is a vascular biomaterial used in cardiovascular surgery that is typically cross-linked for masking antigenicity and enhance stability. There is a need for biochemical evaluation of the tissue properties prior to implantation to ensure that quality and reliability standards are met. Here, engineered antigen removed BP (ARBP) that was cross-linked with 0.2% and 0.6% glutaraldehyde (GA), and further calcified in vitro to simulate graft calcifications upon implantation was characterized nondestructively using fluorescence lifetime imaging (FLIm) to identify regions of interest which were then assessed by Raman spectroscopy. We observed that the tissue fluorescence lifetime shortened, and that Raman bands at 856, 935, 1282, and 1682 cm-1 decreased, and at 1032 and 1627 cm-1 increased with increasing GA cross-linking. Independent classification analysis based on fluorescence lifetime and on Raman spectra discriminated between GA-ARBP and untreated ARBP with an accuracy of 91% and 66%, respectively. Pearson's correlation analysis showed a strong correlation between pyridinium cross-links measured with high-performance liquid chromatography and fluorescence lifetime measured at 380-400 nm (R =-0.76, p = 0.00094), as well as Raman bands at 856 cm-1 for hydroxy-proline (R =-0.68, p = 0.0056) and at 1032 cm-1 for hydroxy-pyridinium (R = 0.74, p = 0.0016). Calcified areas of GA cross-linked tissue showed characteristic hydroxyapatite (959 and 1038 cm-1) bands in the Raman spectrum and fluorescence lifetime shortened by 0.4 ns compared to uncalcified regions. FLIm-guided Raman imaging could rapidly identify degrees of cross-linking and detected calcified regions with high chemical specificity, an ability that can be used to monitor tissue engineering processes for applications in regenerative medicine.
CRIS-Team Scopus Importer:2023-04-20